Factors affecting utilization of dental health services and satisfaction among adolescent females in Riyadh City - Al-Hussyeen, Al Johara A. (The Saudi dental journal, 2010)
This study was conducted to determine factors affecting utilization of dental health services among intermediate female school students in Riyadh. In addition to assessing their satisfaction with the dental care received during the last dental visit. Self-administered questionnaires were distributed among students attending eight public and four private schools. These schools were selected randomly to represent the four different administrative zones in Riyadh. Of 600 questionnaires distributed, 531 were complete and suitable for analysis. Nearly three quarters of the students visited the dentist more than once during the last 2years. A bout 75% had their treatment in private dental clinics and 63% made their visits for routine treatment. The quality of dental care was found to be the most encouraging factor for utilization of dental services, whereas, far geographic location of the dental clinics was the most discouraging factor. For those who received treatment in the government clinics, the most discouraging factor was post operative complications (P<0.0001), while the most encouraging factor was the availability of friendly staff (P<0.0001). The high cost of dental care was the most discouraging factor for utilizing the dental services for those who visited private clinics (P<0.0001), while the high quality of dental care was the most encouraging factor (P<0.009). Students who made their visits because of pain highly considered modern clinics and those recommended by friends as highly encouraging factors (P<0.002), while they considered the high cost of dental care as discouraging factor for using dental services (P<0.038). Students who visited the dentist for routine treatment gave the quality of dental care as encouraging for the use of dental clinics (P<0.0001). Satisfaction with dental care was found to be significantly associated with high quality of dental care, convenient appointment, friendly staff, modern dental clinics and clinics recommended by friends. Quality of dental care, reasonable fees for dental services and close location of dental clinics to students’ homes are encouraging factors for utilization of dental services.